The Predictive Value of the Hemostasis Parameters in the Development of Preeclampsia - Ho, Chao-Hung; Yang, Zwa-Ling (Thrombosis and Haemostasis, 1992)
In order to find out which hemostasis parameters would have the predictive value for the development of preeclampsia, modified antithrombin III (ATM, representative of the antithrombin Ill-serine esterase complex), tissue plasminogen activator (tPA), plasminogen activator inhibitor-1 (PAI-1), beta-throm-boglobulin (BTG), antithrombin III (AT III), fibrinogen, fibrin(ogen) degradation product (FDP), FDP D-dimer and euglobulin lysis time (ELT) were measured in 20 normal nonpregnant women, 21 normal pregnant women, 6 high-risk pregnant women, 14 preeclampsia pregnant women, and 5 patients with disseminated intravascular coagulation (DIC). Only tPA and AT III were found significantly different between the preeclampsia and the normal or high-risk pregnant women: tPA was found progressively and significantly increased from the normal pregnant, to the high-risk pregnant, then to the preeclampsia women (p <0.05). AT III was significantly lower in the preeclampsia than in the normal pregnant (p = 0.0001) or in the high-risk pregnant women (p = 0.002). In the 2nd trimester, tPA, PAI, fibrinogen and FDP were significantly higher, and AT III was significantly lower in the preeclampsia than in the normal pregnant women, whereas in the 3rd trimester, tPA and AT III were significantly higher or lower, respectively, in the preeclampsia than in the normal pregnant women. No significant difference of ATM could be found between the preeclampsia and the normal or high-risk pregnant women. From the present study, we suggest that tPA and AT III would be used as the main predictors, and FDP and D-dimer as the complementary predictors for the development of preeclampsia and should be detected in the normal or high-risk pregnant women.